2015
DOI: 10.1515/sjph-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Patient’s Socio-Demographic Characterictics, Comorbidities and Attitudes on Flu Vaccination Uptake in Family Practice Settings / Vpliv Bolnikovih Psihosocialnih Značilnosti, Komorbidnosti In Stališč Na Odločitev O Cepljenju Proti Gripi V Ambulantah Družinske Medicine

Abstract: ObjectivesIn Slovenia, the role of family physicians in primary care and preventive procedures is very important. Influenza vaccination rates in Slovenia are low. The reasons for low vaccination rates in Slovenia were not clear. We suppose that patient’s beliefs and attitudes are important factors. We assessed patients’ opinions regarding the acceptance of flu vaccination by their family physicians and their beliefs and attitudes about flu and vaccination. The aim was to check out factors that influence the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In fact, poor uptake of the influenza vaccine is a problem around the world, as reported in studies conducted in Lebanon, 8 Jordan, 9 , 10 and European countries. 5 , 6 , 14 In our study, the rate of vaccination is insufficient to achieve a coverage that offers community-wide protection from the disease and its complications. This indicates a need for greater efforts to educate people about the vaccination, and to provide the necessary health facilitation and involvement of multidisciplinary teams to promote the seasonal influenza vaccination.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In fact, poor uptake of the influenza vaccine is a problem around the world, as reported in studies conducted in Lebanon, 8 Jordan, 9 , 10 and European countries. 5 , 6 , 14 In our study, the rate of vaccination is insufficient to achieve a coverage that offers community-wide protection from the disease and its complications. This indicates a need for greater efforts to educate people about the vaccination, and to provide the necessary health facilitation and involvement of multidisciplinary teams to promote the seasonal influenza vaccination.…”
Section: Discussionmentioning
confidence: 77%
“…In comparison, in the Lebanese study, participants most frequently reported that their physician was their main source of information about the influenza vaccine. 5 Similarly, in the Slovenian study, 5 most participants said they received their information about the influenza vaccine from their family physician. It is interesting that most participants in our study said they were concerned about influenza infection and believe that the vaccine is useful to prevent it, yet the majority never get vaccinated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a study in Makkah conducted on adults visiting a primary health care center reported a vaccination rate of only 18.5% [ 10 ]. Various studies reported multiple factors influencing vaccination uptake including knowledge and attitude contributed to the individual's opinions [ 11 ]. In a study in Lebanon, “thinking that the vaccine was not needed” was the only factor associated with lack of receiving the annual influenza vaccine [ 8 ].…”
Section: Introductionmentioning
confidence: 99%